Enantioselective synthesis of syn-2-amino-1, 3-diols via organocatalytic sequential oxa-Michael/α-amination reactions of α, β-unsaturated aldehydes. Issue 23 (8th June 2016) - Weng, Jiang; Huang, Lin-Jie; Long, Liang; Xu, Ling-Yi; Lu, Gui
Graphical abstract: Highlights: A one-pot sequential oxa-Michael/α-amination reaction has been described. Highly enantioenriched syn -β, γ-functional alcohols were obtained. (+)-Safingol and d - threo -clavaminol H were prepared with this method as key step. Abstract: A general and efficient method for the enantioselective synthesis of syn -2-amino-1, 3-diols is reported. It involves the methodology of secondary amine-catalyzed one-pot sequential oxa-Michael/α-amination reactions of α, β-unsaturated aldehydes. This method has also been successfully applied to highly efficient total syntheses of (+)-safingol and d - threo -clavaminol H with excellent stereoselectivities.